Pengelompokan Bidang Usaha Terhadap Bantuan Produktif Usaha Mikro (BPUM) Berdasarkan Wilayah Deli Serdang Menggunakan Metode Clustering K-Means (Studi Kasus: Dinas Koperasi Dan UMKM Kabupaten Deli Serdang) - Tiara Jelita; Relita Buaton; Magdalena Simanjuntak (Forum Kerjasama Pendidikan Tinggi, 2023)
Micro Business Productive Assistance is a program that is assistance from the government to MSME workers throughout Indonesia. Every year, MSMEs can receive this assistance, without exception for those who have received it in previous years. The Office of Cooperatives and MSMEs of Deli Serdang Regency is a regional apparatus in North Sumatra Province which has the main task of carrying out government affairs in the field of cooperatives and small businesses including saving and loan business permits, empowerment and development of small businesses. Micro, Small and Medium Enterprises (MSMEs) are individual business entities which contributed significantly to increasing exports, increasing and equalizing income, forming national products and expanding employment opportunities. Based on these conditions, the authors provide a solution that needs to be built a clustering that can classify fields in each business owned by the community, because not all types of business fields in the community will receive this assistance, including agriculture and animal husbandry. Grouping data can apply the data mining process with the K-Means Algorithm clustering method which is a process of processing very large amounts of data using statistical methods, mathematics, and utilizing Artificial Intelligence technology to produce a group of data. By utilizing the data mining process using the clustering method, it is hoped that clustering can solve the problem of grouping business fields owned by the community. From the test results with 1004 data, which was carried out with MATLAB, it was found that group 1 had 383 data, group 2 had 261 data and group 3 had 360 data. Meanwhile, based on the results of the trial with RapidMiner, it was found that group 1 had 371 data, group 2 had 281 data and group 3 had 352 data.